Cases of Atypical Lymphangiomas in Children - Prashant K. Minocha; Lakhan Roop; Rambachan Persad (Hindawi Limited, 2014)
Background. Lymphatic malformations or lymphangiomas are rare benign hamartomas that result from maldevelopment of primitive lymphatic sacs. They are most frequently found in the neck and axilla, while intra-abdominal and mediastinal lymphangiomas are uncommon. These are primarily tumours of infancy and childhood and are successfully treated with surgical excision. Summary of Cases. Five cases of lymphangioma comprising three intra-abdominal lymphangiomas and two unilateral axillary lymphangiomas presenting at one institution in Trinidad W.I. between 2005 and 2012 were examined. The presentations, location, workup, treatment, and outcome of these patients were studied. Conclusion. This paper discusses a range of extracervical lymphangioma cases seen at San Fernando General Hospital, Trinidad W.I. We report three intra-abdominal cases and the most common clinical presentations were abdominal pain and distension. Also two axillary cases were reported, which presented as painless axillary masses. The major concerns for excision of axillary lymphangioma by parents and surgeons were cosmesis and feasibility of complete resection without disruption of developing breast tissue and axillary vessels. We believe that ultrasound scan is very good at detection of the lesion, while CT is better at determining tumour content and planning for the operation. It is our opinion that complete surgical excision can be achieved.